2019
DOI: 10.1002/jcp.29412
|View full text |Cite
|
Sign up to set email alerts
|

Wortmannin targeting phosphatidylinositol 3‐kinase suppresses angiogenic factors in shear‐stressed endothelial cells

Abstract: Modifications on shear stress‐based mechanical forces are associated with pathophysiological susceptibility and their effect on endothelial cells (EC) needs to be better addressed looking for comprehending the cellular and molecular mechanisms. This prompted us to better evaluate the effects of shear stress in human primary venous EC obtained from the umbilical cord, using an in vitro model to mimic the laminar blood flow, reaching an intensity 1–4 Pa. First, our data shows there is a significant up‐expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…2 and 3). Finally, to test the hypothesis that PI3K/AKT drives angiogenic factors in response to the Ti-enriched medium, we subjected the cells to a chemical inhibition of PI3K using well-known Wortmannin, as it is widely proposed by others [43], and further investigated the behavior of VEGF (Fig. 4a), VEGFR1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3). Finally, to test the hypothesis that PI3K/AKT drives angiogenic factors in response to the Ti-enriched medium, we subjected the cells to a chemical inhibition of PI3K using well-known Wortmannin, as it is widely proposed by others [43], and further investigated the behavior of VEGF (Fig. 4a), VEGFR1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we reasonably suggest that PI3K/AKT signaling participates in the angiogenic phenotype of ECs responding to the Ti-enriched medium. We previously reported that the major mechanotransduction pathway activates PI3K, which plays a pivotal role in guaranteeing EC phenotype and vascular homeostasis [43], and Ti-release displays a very similar effect, mainly in response to Wo/DAE.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we repurposed Wortmannin as a candidate drug that can inhibit PI3K signaling and receptor tyrosine kinase (ERBB4) mediated macropinocytosis, to control virus-cell proliferation and may enhance ERBB4 functions namely alveolarization, morphogenesis, and AEC2 differentiation. Wortmannin is a covalent inhibitor of phosphatidylinositol-3-kinase (PI3K) and related enzymes include the mammalian target of rapamycin (mTOR), DNA-dependent protein kinase catalytic subunit (DNA-PKcs), and mitogen-activated protein kinase (MAPK) 94,95 . In humans, PI3K activates cell signaling pathways in the head and neck, urinary tract, cervical, ovarian, and lung cancer.…”
Section: Precision Based Therapeutic Countermeasures For Covid-19 Patientsmentioning
confidence: 99%
“…3-methyladenine (3-MA) is one of the first used inhibitors of autophagy (Xie et al, 2016), under starving conditions it suppresses autophagy by inhibiting phosphatidylinositol 3kinase, catalytic subunit type 3 (PI3KC3), on the other hand, with nutrients it favors autophagy by using PI3KC1 inhibition (Laha et al, 2019). Because 3-MA was shown to be effective only at high doses, other derivatives were investigated, as Wortmannin, a fungal metabolite that binds to the catalytic site of PI3Ks, and SF1126 (Gomes et al, 2019;Qin et al, 2019). SF1126 is a novel and potent dual inhibitor of phosphatidylinositol 3-kinase and bromodomain-containing protein 4 oncogenes.…”
Section: New Autophagy Inhibitors For Cancer Treatmentmentioning
confidence: 99%
“…Here we will review literature acquisitions concerning the use of liposomes to improve the bioavailability of autophagy inhibitors. Once at the target the drug can be release passively or upon a trigger that can originate from the microenvironment, for example the acidic environment of tumor tissues, or by the outside (light, temperature, magnetic field, ultrasounds) (Needham et al, 2000;Alhmady et al, 2012;Chen et al, 2013;Adriyanov et al, 2014;Luo et al, 2016a;Luo et al, 2016b). Passive release does not require further liposome functionalization, whereas in the case of triggered release liposome have to be engineered ad hoc.…”
Section: Liposomes As An Alternative Strategy Against Autophagy-relatmentioning
confidence: 99%